Differential Stress Responses to Rice Blast Fungal Infection Associated with the Vegetative Growth Phase in Rice - Takuma Koyama; Takumi Tezuka; Atsushi J. Nagano; Jiro Murakami; Takanori Yoshikawa (Plants)
During vegetative growth, plants undergo various morphological and physiological changes in the transition from the juvenile phase to the adult phase. In terms of stress resistance, it has been suggested that plants gain or reinforce disease resistance during the process of maturation, which is recognized as adult plant resistance or age-related resistance. While much knowledge has been obtained about changes in disease resistance as growth stages progress, knowledge about changes in plant responses to pathogens with progressing age in plants is limited. In this study, we experimentally compared rice blast resistance in rice leaves sampled from plants at different growth phases. The results indicate differential infection progression and fungal status depending on growth stage. Transcriptome analysis following blast fungus infection revealed that several genes involved in the defense response were upregulated in both the juvenile and intermediate stage, but the expression changes of many genes were growth phase-specific. These findings highlight differences in rice leaf stress responses to blast infection at different growth stages.